Optimisasi Produksi α-Amilase dari Saccharomycopsis fibuligera R64 dengan Response Surface Method-Central Composite Design (RSM-CCD) - Agus Safari; Ahsanul Chaliqin Gayo; Saadah Diana Rachman; Muhammad Yusuf; Safri Ishmayana (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2019)
α-Amilase (EC 3.2.1.1) is an endoamylase that hydrolyze α-1,4 glycosidic bond in amylose and amylopectin molecules yielding simpler carbohydrate. This enzyme is used to replace starch acid hydrolysis in industrial process. α-Amilase is used in many industrial processes including food, paper, bioethanol, and desizing in textile industries. This enzyme can be found in human, plants and microbes. Most industries use microbes due to their flexibility and require less space and time to culture. In the present study we use Saccharomycopsis fibuligera R64 since this yeast has high amylolytic activity and known as food borne microorganisms. Extrinsic factors are easy to manipulate in the process of enzyme production. The present study intended to determine the optimum condition for α-amylase production by S. fibuligera R64 with agitation speed, pH, and time of incubation as independent variable in the present experiment. The experiment was initiated by rejuvenation of S. fibuligera culture, design of experiment using response surface method, analysis of amylase activity, and determination of protein content. The result of the present study showed that optimum condition for amylase production using S. fibuligera R64 is at pH, agitation speed and incubation time of 3.82, 156 rpm and 49 hours, respectively. The specific activity achieved was 423.8 U/mg based on Fuwa assay.